WISATA KONVENSI : POTENSI GEDE BISNIS BESAR - Nugroho, Tri (Sekolah Tinggi Pariwisata AMPTA, 2014)
MICE (Meeting, Incentive, Conference, Exhibition) in this time still represent the potential market of tourism in Yogyakarta. At the moment more‘s a lot of activity of MICE performed inYogyakarta, is so that expected in a period to coming Yogyakarta become the target of MICE after Bali. With the existence of the growth wisata MICE, hence hotel in Yogyakarta of both for have there is and also which in the process of out for development make the meeting room (Ballroom) which can accomodate until 2.500 visitor Some hotel ready to for example Prodigal of Ambarruko Hotel, Sahid Rich Hotel, propose the readily Tentrem Hotel bicaming Yogyakarta as town of target MICE, with the goals 65% activity MICE and 35% guest from Travel Agent (Kompas com. 28 June 2014). Keywords: MICE, Hotel, Tourism Service, MICE School.